Integritas Pemilu, Klienelisme Politik, dan Legitimasi Kepemimpinan: Analisis Sosiologi Hukum Islam terhadap Pemilihan Presiden di Indonesia: Electoral Integrity, Political Clientelism, and Leadership Legitimacy: An Islamic Sociological Jurisprudence Analysis of Presidential Elections in Indonesia - Ridhwan Bakhtiar; Fathia 'Ilma Nafi'a; Zidni Nur Fatimah; Shandy Errlita; Nurul Nurjannah; Maeva Fatia Salma; Mila Nur Rosita; Ahmad Muhammad Mustain Nasoha (LITERA: Jurnal Ilmiah Mutidisiplin, 2026)
This study analyzes the presidential election in Indonesia from the perspective of Islamic sociological jurisprudence (fiqh al-sociology), focusing on electoral integrity, political clientelism practices, and leadership legitimacy. The primary issue examined is the widespread prevalence of money politics, the politicization of social assistance, political brokerage, and patronage relationships that undermine the quality of democracy and public trust in election outcomes. This research employs a qualitative method with a literature review approach, analyzing relevant books, journals, and scientific sources. The results indicate that political clientelism has become a serious threat to electoral integrity by shifting programmatic competition into transactional interests. This condition also weakens leadership legitimacy, as the political mandate obtained does not entirely emerge from the free and rational choices of the public. From the perspective of Islamic sociological jurisprudence, these phenomena contradict the principles of amanah (trustworthiness), justice, shura (consultation), and maslahah (public interest). Therefore, it is necessary to strengthen political education, enforce electoral laws, enhance the integrity of election organizers, and internalize Islamic values within society's political culture.